2013
DOI: 10.25011/cim.v36i6.20627
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of body mass index in breast cancer patients with hormone receptor-positive tumours after curative surgery

Abstract: Purpose: Obesity has been recognized as a significant risk factor for postmenopausal breast cancer. The aim of this study is to investigate the prognostic significance of body mass index (BMI) in hormone receptor-positive, operable breast cancer. Methods: In this retrospective cohort study, 1,192 consecutive patients with curative resection of primary breast cancer were enrolled. Patients were assigned to two groups according to BMI: normal or underweight (BMI < 23.0 kg/m2) and overweight or obese (BMI ≥23… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 36 publications
1
6
0
Order By: Relevance
“…In our study, we found significant differences in DFS, BCSS, and OS through a multivariate analysis and each of these variables was an independent predictor of PR status, chemotherapy, lymph node metastasis, and factors, which is similar to results of previous studies [22232425]. Kakugawa et al [26] suggested that decreased PR expression might lead to excessive proliferation of glandular cells, which can cause cancer and metastatic lesions.…”
Section: Discussionsupporting
confidence: 90%
“…In our study, we found significant differences in DFS, BCSS, and OS through a multivariate analysis and each of these variables was an independent predictor of PR status, chemotherapy, lymph node metastasis, and factors, which is similar to results of previous studies [22232425]. Kakugawa et al [26] suggested that decreased PR expression might lead to excessive proliferation of glandular cells, which can cause cancer and metastatic lesions.…”
Section: Discussionsupporting
confidence: 90%
“…After searching and screening all eligible studies, 20 retrospective cohort studies including 33,836 patients with EBC 14 , 18 , 21 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 were selected; one study 44 was only published in abstract form. Of the 20 retrospective cohort studies included, 12 studies each examined the effects of overweight on DFS and OS, 12 and 15 studies examined the effects of obesity on DFS and OS, respectively, and 16 and 17 studies examined the effects of high BMI on DFS and OS, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Of the included 20 retrospective cohort studies, 16 studies 18 , 21 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 41 , 43 , 44 , 45 , 46 reported data on DFS, 17 studies 14 , 18 , 21 , 30 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 45 reported OS data, and 14 studies 18 , 21 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 41 , 42 , 43 , 44 , 45 reported both endpoints. However, three studies 21 , 30 , 31 reported RFS data, and one study 32 reported EFS data.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations